Money, myths, and change: the economic lives of lesbians and gay men - Badgett, Mary Virginia Lee (Worlds of desire, 2001)
How does the standard of living of gay men and lesbians compare with that of heterosexuals? Do homosexuals make financial and family decisions differently? Why are the professional lives of gay men and lesbians dissimilar from those of heterosexuals? Or do they even differ? Have gay people benefited from the recent economic boom? Or have public policies denied them their fair share? Money, Myths, and Change provides new answers to these complex questions. This is the first comprehensive work to explore the economic lives of gays and lesbians in the United States. M. V. Lee Badgett weaves through and debunks common stereotypes about gay privilege, income, and consumer behavior. Studying the ends and means of gay life from an economic perspective, she disproves the assumption that gay men and lesbians are more affluent than heterosexuals, that they inspire discrimination when they come out of the closet, that they consume more conspicuously, that they enjoy a more self-indulgent, even hedonistic lifestyle. Badgett gets to the heart of these misconceptions through an analysis of the crucial issues that affect the livelihood of gay men and lesbians: discrimination in the workplace, denial of health care benefits to domestic partners and children, lack of access to legal institutions such as marriage, the corporate wooing of gay consumer dollars, and the use of gay economic clout to inspire social and political change. Both timely and readable, Money, Myths, and Change stands as a much-needed corrective to the assumptions that inhibit gay economic equality. It is a definitive work that sheds new light on just what it means to be gay or lesbian in the United States.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; capitalisme; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; shm4000; systèmes d'oppressions; thématiques; travail; états-unis

Femmes et médias à travers le monde pour le changement social - Delanoë, Maryvon; Centre de documentation sur l'éducation des adultes et la condition féminine; WomenAction 2000 (Éditions du remue-ménage, 2001)
Face à un paysage médiatique mondial à prédominance masculine dans lequel l’information diffusée est trop souvent sexiste, stéréotypée et uniforme, comment les femmes parviennent-elles à prendre la place qui leur revient? Voici un tour du monde des réalisations de femmes dans le domaine des médias, qui signale les obstacles auxquels elles se heurtent dans chaque région du globe mais qui présente également plus de 40 stratégies novatrices qu’elles ont mises en |uvre pour produire une information plus équilibrée et représentative. Parmi celles-ci, on note des documents multimédias pour les Africaines en milieu rural, une agence de presse féministe au Mexique, une radio communautaire au Timor Oriental, un réseau Internet pour la paix en Macédoine, etc.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; com5170; cours; discipline; histoire et politique; justice sociale; militance; premier cycle; pédagogie; périodes historiques; représentation des femme*; sciences de l'éducation; thématiques; travail